THE EFFECT OF USING THE PIRATES OF THE CARIBBEAN GAME ON GRADE 5 STUDENTS’ VOCABULARY MASTERY - Martin Maradani Lasut (Widya Mandala Surabaya Catholic University, 2015)
In English classes, teachers believe that vocabulary plays an important role in building students’ English skills. Unfortunately, they do not give much attention to how to teach vocabulary in an attractive and fun way by using games. Teachers seem to use the old fashioned way of teaching, by giving a word list and asking students to memorize it. This research explored the usage of game, The Pirates of Caribbean Game, in teaching vocabulary to students. Did students taught by using game get better score than those who were taught by word list? In answering this question, the researcher used quasi experimental research, pre-test and post-test given to the control and experimental groups. After giving the treatment for five times, the research finally showed there was no significant difference in using the word list and The Pirates of Caribbean game.